2021
DOI: 10.3389/fmats.2021.737749
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Aluminum Diethylphosphinate on Thermal Stability, Flame Retardancy, and Mechanical Properties of Poly(butylene succinate)

Abstract: Poly(butylene succinate) is one of the most promising biodegradable polymers, but its applications are limited by poor flame retardancy. In this work, poly(butylene succinate)/diethylphosphinate (PBS/AlPi) composites were fabricated to investigate the effect of AlPi on their thermal stability, flame retardancy, and mechanical properties. It was found that the high content of AlPi decreased the thermal stability of PBS, and the decrease became stronger under the air atmosphere. When the content of AlPi reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The TGA curve of PBS followed single-step degradation and decomposition of the polymer chain backbone (Figure 1B), with a T max of 394.5 • C (Table 2). A T max of 403.2 • C was reported by Wang, et al [38]. For RES, two main weight-loss stages were observed.…”
Section: Thermal Propertiesmentioning
confidence: 66%
See 1 more Smart Citation
“…The TGA curve of PBS followed single-step degradation and decomposition of the polymer chain backbone (Figure 1B), with a T max of 394.5 • C (Table 2). A T max of 403.2 • C was reported by Wang, et al [38]. For RES, two main weight-loss stages were observed.…”
Section: Thermal Propertiesmentioning
confidence: 66%
“…The TGA curve of GRA showed insignificant weight loss until 550 • C, revealing its thermal stability. In a study conducted by Wang et al [38] the DTG curve of GRA was presented, covering a temperature range from 40 to 500 • C with minimal weight loss. However, at higher temperatures, specifically from 500 to 1000 • C, the authors observed two distinct events.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Phosphorus-based compounds, which exhibit high flame retardancy and low toxicity, have found wide use, [19][20][21] such as ammonium polyphosphate-based expansion systems, [22][23][24] aluminum hypophosphite and aluminum diethyl phosphonate. [25][26][27] However, flame retardants containing phosphorus often lead to a significant accumulation of heat during combustion, which causes increased smoke release. 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) has been discovered to reduce the heat of combustion by absorbing free radicals during combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown a longstanding interest in modifying PBS to improve its flame resistance. Phosphorus‐based compounds, which exhibit high flame retardancy and low toxicity, have found wide use, 19–21 such as ammonium polyphosphate‐based expansion systems, 22–24 aluminum hypophosphite and aluminum diethyl phosphonate 25–27 . However, flame retardants containing phosphorus often lead to a significant accumulation of heat during combustion, which causes increased smoke release.…”
Section: Introductionmentioning
confidence: 99%
“…It can be expected that the dynamic feature of MDOPs should enable the exchange of monomeric units in solution and generate supramolecular copolymers MDOPs and their structural analogues with phosphinate bridging ligands have already been successfully utilized in several areas of modern materials science and engineering. For example, these types of 1D coordination polymers have been used as effective flame retardants [23][24][25][26][27][28], reinforcing fillers in polymer composites [14,[23][24][25]28,29], organogelators [30][31][32], as well as components of smart materials that change their properties under the influence of external stimulants (e.g., magnetic or electric field) [21,33,34]. One of the main obstacles to the broader use of MDOPs as materials for new technologies is the lack of information about changes in their molecular structure and morphology under the influence of temperature, solvents or other factors that may affect the durability of bridging bonds between metal centers.…”
Section: Introductionmentioning
confidence: 99%